Can we use qualitative research approach in biomedical studies? - Joshi, S (Journal of Institute of Medicine Nepal, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, August, 2009; 31:2 1-2